Quinolone Derivatives as Anticancer Agents: Importance in Medicinal Chemistry - Azzman, Nursyuhada; Anwar, Sirajudheen; Syazani Mohamed, Wan Ahmad; Ahemad, Nafees (Current Topics in Medicinal Chemistry, 2024)
Quinolone is a heterocyclic compound containing carbonyl at the C-2 or C-4 positions with nitrogen at the C-1 position. The scaffold was first identified for its antibacterial properties, and the derivatives were known to possess many pharmacological activities, including anticancer. In this review, the quinolin-2(H)-one and quinolin-4(H)-one derivatives were identified to inhibit several various proteins and enzymes involved in cancer cell growth, such as topoisomerase, microtubules, protein kinases, phosphoinositide 3-kinases (PI3K) and histone deacetylase (HDAC). Hybrids of quinolone with curcumin or chalcone, 2-phenylpyrroloquinolin-4-one and 4-quinolone derivatives have demonstrated strong potency against cancer cell lines. Additionally, quinolones have been explored as inhibitors of protein kinases, including EGFR and VEGFR. Therefore, this review aims to consolidate the medicinal chemistry of quinolone derivatives in the pipeline and discuss their similarities in terms of their pharmacokinetic profiles and potential target sites to provide an understanding of the structural requirements of anticancer quinolones.
Keywords: Small molecules